AURAL FOREIGN BODIES: A RETROSPECTIVE STUDY OF 162 PATIENTS. - Stephen AgbomhekheOgah (ziauddin University, 2024)
Background: Foreign bodies in the ear are relatively common in the practice of otology. Children below 10 years of age are usually more involved than adults. The physical characteristics of these foreign bodies will determine the mode and the instrument required for their removal. Objectives: To determine the types of foreign bodies, age commonly involve, method of removal of aural foreign bodies (with or without anesthesia) and complications associated. Methodology: This is a 5-year retrospective study conducted at the Otolaryngology Unit of the Department of Surgery Federal Medical Centre Lokoja. After obtaining a written permission from the Hospital Medical Records Department, patient's data such as age, sex, presentation and duration of symptoms, treatment modality and outcome were extracted, studied and analyzed. Results: Eventually 162 patients with the age range from 1 to 60 years, a mean age of 8.14 years, and a modal age of 1-10 years underwent analysis. Of all patients, Seeds/grains 41(25.3%) were the commonest foreign bodies found in this study, followed by beads 36(22.2%). Furthermore, it was found that 95.1% of foreign bodies were removed in clinic without anesthesia and six patients (3.7%) had complications such as tympanic membrane perforation 2(1.3%), external auditory canal bruises 2(1.3%), hearing loss 1(0.6%) and acute mastoiditis 1(0.6%). Conclusion: In conclusion, we found thatgrains, seeds and beads form the bulk of aural foreign bodies encountered mostly in children while cotton, matchsticks and insects are common in the adults. With the right kind of instrument, an ENT Specialist can successfully remove 95% of these foreign bodies without anesthesia and less complications.